The antecedents of supply chain technology adoption among the SMEs in Johor Bahru - Wee, Sin Yi 1989- author; Noriza Mohd. Jamal, supervisor; Inda Sukati, supervisor; Fakulti Pengurusan (2014)
Thesis (Sarjana Pengurusan (Teknologi)) - Universiti Teknologi Malaysia, 2014